Pengaruh Social Media (Content Creation, Content Sharing, Connecting, Community Building) Terhadap Keputusan Pelanggan Pada Produk IndiHome (Studi kasus Witel Telkom Pasuruan Jawa Timur) - Farida Karimatun Nisa’; Rois Arifin; Kartika Rose Rachmadi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and explain the effect of social media marketing (Content Creation, Content Sharing, Connecting, Community Building) on customer decisions on IndiHome products (Special Study of Wittel Telkom Pasuruan). This research includes a type of research with quantitative. The method used is multiple linear regression. The sampling technique uses the formula from Solvin with the calculation results of 91 samples. To solve the problems in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously The variables Content Creation (X1), Content Sharing (X2), Connecting (X3), Community Building (X4), have a significant simultaneous effect on customer decisions on IndiHome Telkom products (Y). And there is a partial influence between Content Creation (X1), Content Sharing (X2), Connecting (X3), Community Building (X4), on Customer Decisions on IndiHome Telkom Products (Y). Keywords : Content Creation, Content Sharing, Connecting. Community Building,CustomerDecisions